Depression, Anxiety, and Stress Symptoms among Football Players in Iceland: The Effects of Injuries, Overtraining and Insecurity - María Mjöll Björnsdóttir 1995- (2018)
The prevalence of mental disorders in athletes has remained unclear and an inconsistency has occurred between studies of whether the prevalence is higher, lower or similar to the general public. However, research has indicated several risk markers related to an increase in the prevalence of mental disorders such as depression, anxiety, stress and eating disorders. Factors such as suffering from injuries, overtraining and insecurity has been found to be related to an increase in mental disorders. The present research aimed to study the prevalence of depression, anxiety and stress among football players in Iceland and potential risk markers. The participants of the study were 254 football players from six of the 13 clubs that compete in Iceland's top league, Pepsi-league, and either played for the first team, or the under 20s team. Males were 63% and female 37%. The results of the study indicated a great difference between the genders. Furthermore, it revealed a strong relation between insecurity, as well as dissatisfaction with the club with a higher prevalence of depression and anxiety. However, inconsistent with former research, injuries and overtraining had a weak relation with anxiety, depression, and stress. Keywords: mental health, football players, injuries, overtraining, insecurity Litlar upplýsingar eru um nákvæma tíðni yfir geðraskanir á meðal íþróttafólks og hafa rannsóknir ýmist leitt í ljós hærri, lægri eða svipaða tíðni geðraskana á meðal íþróttamanna annars vegar og almennings hins vegar. Þrátt fyrir ósamræmi á milli rannsókna hafa þær þó leitt í ljós að ákveðnir umhverfisþættir íþróttamanna geta leitt til aukinnar tíðni geðraskana líkt og þunglyndi, kvíða, streitu og átraskana. Þeir þættir eru meðal annars meiðsl íþróttamanna, of mikið líkamlegt álag og óöryggi. Aðalmarkmið þessarrar rannsóknar var að kanna tíðni þunglyndis, kvíða og streitu hjá knattspyrnufólki á Íslandi og mögulega áhættuþætti. Þátttakendur voru samtals 254 knattspyrnumenn og -konur sem komu frá sex af þeim 13 knattspyrnuliðum ...